Desapropriação indireta entre os entes federativos - Araújo, Filipe Autran Cavalcante (2010)
The present study analyses the viability and the consequences of the indirect expropriation between the federative entities. It is well known as a controversial subject. After all, the expropriation treated herein, despite being manifestly contrary to the Brazilian legal system, is widely employed, and not as rare as one could imagine. The study intends, therefore, to determine a reasonable solution for such consummated and irreversible situation, in which the legitimate public interest, among the others administrative and constitutional principles, are minimally affected.